School Principal's Efforts To Improve Teacher Performance Through Clinical Supervision At MAN 1 Bojonegoro, East Java, Indonesia - Wahib , Abd. (International Journal of Educational Research & Social Sciences, 2024)
Clinical supervision is professional human assistance provided to teachers who experience problems in learning so that the teacher concerned can overcome the problem by taking systematic steps including the planning stage, the observation stage of teacher teaching behavior, as well as the behavior analysis and follow-up stages. The aim of the research is to determine the school principal's efforts to improve teacher performance through clinical supervision at MAN 1 Bojonegoro, East Java, Indonesia. The research design that will be carried out is using school action research (SAR). The method uses data collection through observation, field notes and documentation. The data analysis techniques used are: (1) data reduction, (2) data presentation, (3) drawing conclusions. The results of the research are: the principal's efforts through clinical supervision carried out on teachers can improve teacher performance as evidenced by the increase in teacher performance from the beginning before the action was 58.2%, after the first cycle action it was 70.1%, and after the second cycle action it increased again to 83.7%. The results of clinical supervision action research on high class teachers were proven to provide an increase in teacher performance which in turn had an impact on improving student learning outcomes.